Toward the rational design of cathode and electrolyte materials for aprotic Li‐CO2 batteries: A numerical investigation. (31st October 2019) - Xiao, Xu; Shang, Wenxu; Yu, Wentao; Ma, Yanyi; Tan, Peng; Chen, Bin; Kong, Wei; Xu, Haoran; Ni, Meng
Summary: A lithium‐carbon dioxide (Li‐CO2 ) battery offers an effective and efficient approach for the simultaneous CO2 capture and electrical energy generation. However, the useful guidance for the electrode design and the electrolyte selection is still lacking. Herein, we carry out numerical analyses on the effects of design parameters on the discharge voltage plateau and specific capacity. The developed mathematical model concentrates on the integration of mass transport with the electrochemical reaction to describe the transport and kinetics progresses. After validated by experimental data, the effects of cathode geometries, electrolyte transport properties, and solid product component on the discharge behaviors are detailedly analyzed. The results reveal an interesting solid product distribution that more is accumulated near two edges and less is in the center of the cathode. For the electrode design, a thinner electrode with a larger porosity is beneficial for a large capacity, and highly active catalysts can diminish the voltage loss and increase the discharge plateau. For the electrolyte selection, it is suggested that higher CO2 solubility and diffusivity is preferred for the high energy density. Further, the hybrid product component with increasing the carbon content or decreasing the solid Li2 CO3 content can lead to more reaction sites. This work gives a valuable direction of parameter selection to facilitate the development of Li‐CO2 batteries.